Systemic Corticosteroid Administration in Coronavirus Disease 2019 Outcomes: An Umbrella Meta-Analysis Incorporating Both Mild and Pulmonary Fibrosis–Manifested Severe Disease - Cheng, Bin; Ma, Jinxiu; Yang, Yani; Shao, Tingting; Zhao, Binghao; Zeng, Linxiang (Frontiers in Pharmacology, 2021)
Background: Effective treatments for coronavirus disease 2019 (COVID-19) are urgently needed. The real role of corticosteroid use in COVID-19 has long been of interest and is disputable. Methods: We aimed to quantitatively reevaluate the efficacy of corticosteroids on COVID-19. Databases were searched for eligible meta-analyses/systematic reviews with available outcome data. For each association, we estimated the summary effect size with fixed- and random-effects models, 95% confidence intervals and 95% prediction intervals. Heterogeneity, Egger’s test, evidence of small study effects and excess significance bias, and subgroup analyses were rigorously evaluated. Results: Intended outcomes of twelve eligible studies were mortality, clinical improvement, hospitalization, mechanical ventilation (MV), adverse events (AEs), intensive care unit (ICU) stay, hospital stay, virus clearance time (VCT), and negative conversion. Corticosteroid administration was associated with a 27% risk reduction in MV (hazard ratio (HR): 0.73 (0.64-0.83) and a 20% reduction in mortality of critically ill/severe COVID-19 patients (HR: 0.80 (0.65-0.98)). Interestingly, shorter ICU stays and, conversely, potentially longer hospital stays, a longer VCT and a longer time to negative conversion were associated with corticosteroid use. There was no significant impact of different corticosteroid doses on mortality. Only one study showed slight excess significant bias. Caution should be applied given the weak nature of the evidence even it has been confirmed by sensitivity analyses. Conclusion: This umbrella study found benefits from corticosteroids on MV, especially the mortality of critically ill/severe patients, with shorter ICU stays but prolonged hospital stays and VCT. The benefits and harms should be reevaluated and balanced before corticosteroids are cautiously prescribed in clinical practice.